Managing Compliance Risk in Organisations in the Transport-Forwarding-Logistics Sector - Winnicka-Wejs, Alicja; Kwarcińska, Agnieszka (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: To analyse and evaluate compliance risk management in organisations operating in the transport-forwarding-logistics (TFL) sector. Research Design & Methods: A comparative analysis of the social reports of TFL companies submitted from 2019 to 2023, considering the issues of compliance risk, compliance management system and whistleblowing mechanisms. Findings: Responding to rapid changes in the law and regulatory risk, the majority of the companies under study include compliance risk as a major risk category. These companies measure compliance risk through the number of whistleblowing reports and an assessment of its materiality on a quantifiable scale. The organisational arrangements of the compliance management system vary according to need, with three member groups in organisations performing the compliance function: top management and lower management, compliance officers, other members of the organisation. Implications / Recommendations: The study findings may come useful for business owners, managers, compliance officers who are responsible for compliance management systems in their organisations. The results obtained from the study indicate the inadequacy of the organisations in terms of compliance management. Therefore, the basic recommendations concern the need to form appropriate attitudes, build awareness of both the importance of compliance risk management and the consequences of the lack of such solutions and the benefits of their implementation. The introduction of regulatory solutions will be an additional stimulus for inducing implementing compliance risk management. Finally, there is a need for compliance education and improved whistleblowing mechanisms to ensure whistleblowers protection against retaliation. Contribution: The article offers insights on the development of management and quality science in the field of compliance management systems and compliance risk management in organisations.